2008
DOI: 10.1371/journal.pone.0003010
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi Complement Regulator-Acquiring Surface Protein 2 Does Not Contribute to Complement Resistance or Host Infectivity

Abstract: Borrelia burgdorferi, the pathogen of Lyme disease, cycles in nature through Ixodes ticks and mammalian hosts. At least five Complement Regulator-Acquiring Surface Proteins (BbCRASPs) are produced by B. burgdorferi, which are thought to assist spirochetes in host immune evasion. Recent studies established that BbCRASP-2 is preferentially expressed in mammals, and elicits robust antibody response in infected hosts, including humans. We show that BbCRASP-2 is ubiquitously expressed in diverse murine tissues, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
93
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 59 publications
6
93
1
Order By: Relevance
“…The protective role of OspA appears to be enhanced by lipidation (for a review, see reference 10). Although CspZ likely contributes to pathogenesis, it does not appear to be absolutely essential for infectivity and virulence (9). In spite of the potential and theoretical promise of vaccines based on FH binding proteins, this study, coupled with earlier analyses, does not elicit optimism regarding the utility of recombinant Borrelia FH binding proteins in development of a vaccine and/or diagnostic assay.…”
Section: Vol 77 2009 Analysis Of the Cspz Protein Of B Burgdorferimentioning
confidence: 75%
See 2 more Smart Citations
“…The protective role of OspA appears to be enhanced by lipidation (for a review, see reference 10). Although CspZ likely contributes to pathogenesis, it does not appear to be absolutely essential for infectivity and virulence (9). In spite of the potential and theoretical promise of vaccines based on FH binding proteins, this study, coupled with earlier analyses, does not elicit optimism regarding the utility of recombinant Borrelia FH binding proteins in development of a vaccine and/or diagnostic assay.…”
Section: Vol 77 2009 Analysis Of the Cspz Protein Of B Burgdorferimentioning
confidence: 75%
“…In panels B and C, the triangles and circles show the results for individual vaccinated and control mice, respectively, and the bars indicate the averages. determinant of dissemination (9). Lastly, it is important to note that Kraiczy et al also recently determined several cspZ gene sequences for B. burgdorferi isolates (26).…”
Section: Vol 77 2009 Analysis Of the Cspz Protein Of B Burgdorferimentioning
confidence: 98%
See 1 more Smart Citation
“…Many of the lipoprotein genes are members of these paralogous families. The loss of one of these lipoproteins of B. burgdorferi can be compensated for by the presence of other paralogous genes in the same family (11,38 …”
Section: Discussionmentioning
confidence: 99%
“…CspA inhibits complement deposition and enhances serum resistance of B. burgdorferi in vitro (8,24). Conversely, CspZ is not surface exposed and is not required for serum resistance or experimental murine infection (12). While Hellwage et al previously reported that a recombinant form of OspE from B. burgdorferi strain N40 can bind FH, the importance of OspE expression on the surface of the organism in relation to serum resistance has yet to be defined (21).…”
mentioning
confidence: 99%